Analisis Daya Anestesi Bahan Alami Ekstrak Buah Keben (Barringtonia asiatica) Pada Ikan Bawal Bintang (Trachinotus blochii) - Cik Mas Edison; Thamrin '; Yusni Ikhwan Siregar (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The experiment was conducted at Marine Aquaculture Unit of UPTD Sub-District of Moro Fishery and Marine Office of Karimun Regency, Province ofKepulauan Riau on February to March 2017. Extraction stage was conducted atMarine Chemical Laboratory Department of Marine Science Faculty of Fisheriesand Marine University of Riau. This Study aims to obtain the optimalconcentration of extract Keben (Barringtonia asiatica) for the process ofimotilization of Silver Pompanoo Fish. The test animal used is Silver Pompanoo(Trachinotus blochii) with size 150-200 gr. On the basis of preliminary results, theexperiment were carried out with 4 treatment concentrations of 13,79 mg/l, 19,00mg/l, 26,00 mg/l, 35,50 mg/l, and 0 mg/l as controls. Anova test showed thatconcentration had significant effect (P<0,05) on induction time, recoveredconscious and survival rate of Silver Pompanoo. The results showed thatconcentration 13,79 mg/l was the optimal concentration for Silver Pompanooimotilization process with induction time ranged from 15-17 minutes andconscious recovering time around 4-5 minutes and long fainting for 4,5 hours andresulted in rate of life equal to 86,6%.Kata Kunci : Barringtonia asiatica, Trachinotus blochii, imotilization.BAB I. PENDAHULUAN1.1. Latar BelakangAnestesi adalah suatu teknikyang dapat